Concrete pictorial abstract approach to the improvement of elementary school students’ self efficacy mathematics - H E Putri; A Yulianto; G Nikawanti; P Rahayu; N W A Majid (Pascasarjana Universitas Pendidikan Indonesia, 2020)
The present study is aimed at investigating the influence of Concrete Pictorial Abstract (CPA) approach to the improvement of elementary school students’ Self Efficacy Mathematics (SEM) seen from Mathematical Prior Ability (MPA) and as a whole. It is a quasiexperiment with control design of pre-scale and post-scale in Mathematics in the topic of 3 dimension geometry (3D geometry) to 119 elementary school students in Purwakarta Subang Karawang Bekasi (Purwasukasi), West Java. The present study is conducted by using two study groups, a group which implements CPA learning approach as the experimental group and group which implements conventional learning as the control group. Both descriptive and inferential data analysis show that the improvement of students’ SEM is better in students with CPA learning approach rather than students with conventional learning, seen as a whole and in every MPA.Therefore, CPA learning can improve elementary school students’ SEM.